If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5-x)=3(14-2x)
We move all terms to the left:
2(5-x)-(3(14-2x))=0
We add all the numbers together, and all the variables
2(-1x+5)-(3(-2x+14))=0
We multiply parentheses
-2x-(3(-2x+14))+10=0
We calculate terms in parentheses: -(3(-2x+14)), so:We get rid of parentheses
3(-2x+14)
We multiply parentheses
-6x+42
Back to the equation:
-(-6x+42)
-2x+6x-42+10=0
We add all the numbers together, and all the variables
4x-32=0
We move all terms containing x to the left, all other terms to the right
4x=32
x=32/4
x=8
| 2x+1+2x+3=84 | | -42+6x=24 | | 0x+4=6x+2 | | 2x•8=4 | | 6p-36=12 | | 650=50x | | -3(x+4)=2(x-3)+34 | | 4(x•2)=12 | | 4(x•2)=12) | | 1/2(h)(9+19)=104 | | h+9=21;10,11,12,20 | | 3x-x-3/4=13 | | -5(2x+8)=-4(3x-11) | | 5x=2x+6= | | 2/5x=-25 | | x-23=-38 | | 3x−2=2x+2 | | 3x+2=6x+13 | | x-(-17)=43 | | -7x+(x-5)=-11 | | 3•(x-5)=-18 | | 3(4s+9)=63 | | 205=53-x | | 3(2l+8)=54 | | (e-8)*9=36 | | (e-6)*5=25 | | 7x+2=121 | | 10+20+2x=60 | | 1/x=17 | | 15+12n=2(n-4) | | 11+4x=0 | | 15-3x=x+9 |